Revitalisasi UMKM Sri Batik Jumput Melalui E-CoDigimark untuk Penguatan Branding Produk Unggulan Bojonegoro - Indriana, Nilna; Nisa', Ida Fauziatun; Dyana, Burhanatut (Jurnal SOLMA, 2026)
Background: Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in Indonesia’s economy, including Sri Batik Jumput MSME, which specializes in jumputan batik and mukena production in Prayungan Hamlet, Medalem Timur, Sumberrejo District, Bojonegoro Regency. Established in 1980 and rooted in local wisdom, this MSME has strong potential but faces challenges in production, management, marketing, and branding that affect its competitiveness and business sustainability. Methods: This community service program aimed to increase the turnover and competitiveness of Sri Batik Jumput MSME by implementing E-CoDigimark (E-Commerce and Digital Marketing). The methods included field surveys, coordination with community partners, and training and mentoring activities involving 30 participants, comprising MSME actors and local women from Prayungan Hamlet. Results: The program indicates improved participants’ knowledge and skills in developing product variations from jumputan batik into mukena, prayer rugs, and tablecloths, with more innovative color variations. Participants also gained skills in attractive product packaging and digital marketing, which increased the products’ market value. These findings were identified through questionnaires completed by participants during the training and mentoring activities. Conclusions: The application of E-CoDigimark enhances MSME capacity to adapt to market competition, expand market reach, and strengthen branding based on local wisdom. This program also contributes to achieving the Sustainable Development Goals (SDGs), particularly No Poverty and Sustainable Industry, and aligns with national strategic policies such as Asta Cita and RIRN in empowering MSMEs through digital technology.